Analisis Efisiensi Saluran Pemasaran Jamur Tiram Putih (Studi Kasus di Desa Banjar Dewa Kecamatan Banjar Agung Kabupaten Tulang Bawang) - Suharta, Kadek Aris Oki; Rahayu, Ni Putu Widhia (Jurnal EMT KITA, 2024)
The aim of this study is to analyze the marketing channels for white oyster mushrooms and the efficiency of marketing channels for white oyster mushrooms in Banjar Dewa Village, Banjar Agung District, Tulang Bawang Regency. This type of study is descriptive qualitative research. The population of all farmers cultivating white oyster mushrooms is 14 people in Banjar Dewa Village, Banjar Agung District, Tulang Bawang Regency, with a sampling technique using Purposive Sampling with a sample of one farmer cultivating white oyster mushrooms with the criteria of producing the largest white oyster mushroom cultivation in the area. The method for collecting data in the following research is observation and interviews. The analysis technique in the following research uses marketing cost analysis, marketing margin, marketing profit, and marketing efficiency. The results of this research show that there are two marketing channel patterns for white oyster mushrooms, namely the first channel pattern, farmers sell white oyster mushrooms directly to end consumers, and the second channel pattern, farmers sell to retailers and then the retailers sell them back to end consumers. The marketing margin value in the first channel pattern is IDR 0, while marketing in the second channel pattern is IDR 11,000. The farmer's share value in the first channel pattern is 100%, the second channel pattern is 56%. The two marketing channels for white oyster mushrooms are said to be efficient in terms of marketing margin and farmer's share. The most efficient marketing channel for white oyster mushrooms is the first marketing channel with the lowest margin value and the highest farmer's share value.